2005
DOI: 10.1111/j.1523-1755.2005.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variance of SGK-1 is associated with blood pressure, blood pressure change over time and strength of the insulin-diastolic blood pressure relationship

Abstract: Our data suggest that SGK-1 risk carriers are at increased risk of hypertension and are more sensitive to the blood pressure elevating effects associated with hyperinsulinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 39 publications
5
61
0
Order By: Relevance
“…Genetic studies in twins indeed revealed a specific SGK1 risk haplotype associated with moderately elevated blood pressure in individuals who simultaneously carry a homozygous genotype for a variant in intron 6 (I6CC) and a homozygous or heterozygous genotype for the C allele of a polymorphism in exon 8 (E8CC/ CT) (81,82). This SGK1 risk haplotype was later confirmed to be associated with hypertension in a large-scale population study of Ͼ4800 Swedish subjects (83).…”
Section: Sgk1mentioning
confidence: 88%
“…Genetic studies in twins indeed revealed a specific SGK1 risk haplotype associated with moderately elevated blood pressure in individuals who simultaneously carry a homozygous genotype for a variant in intron 6 (I6CC) and a homozygous or heterozygous genotype for the C allele of a polymorphism in exon 8 (E8CC/ CT) (81,82). This SGK1 risk haplotype was later confirmed to be associated with hypertension in a large-scale population study of Ͼ4800 Swedish subjects (83).…”
Section: Sgk1mentioning
confidence: 88%
“…Moreover, moderately enhanced blood pressure values are observed in individuals carrying a variant of the SGK1 gene, affecting some 3-5% of unselected Caucasians [9,43]. Interestingly, the gene variant is associated with enhanced insulin sensitivity of blood pressure [43].…”
Section: Discussionmentioning
confidence: 99%
“…The cornerstone of insulin resistance in the metabolic syndrome is a reduced sensitivity to the metabolic actions of insulin (3,4), initially leading to a compensatory increase in the levels of insulin to maintain glucose homeostasis. Indeed, recent findings suggest that raised levels of insulin in the metabolic syndrome stimulate the serumand glucocorticoid-regulated kinase 1 (SGK-1) in effect prolonging the half-life of the epithelial sodium channel which leads to sodium and water retention and raised levels of blood pressure (5).…”
Section: Introductionmentioning
confidence: 99%